Digital breast tomosynthesis and contrast‐enhanced dual‐energy digital mammography alone and in combination compared to 2D digital synthetized mammography and MR imaging in breast cancer detection and classification. Issue 5 (30th December 2019) - Petrillo, Antonella; Fusco, Roberta; Vallone, Paolo; Filice, Salvatore; Granata, Vincenza; Petrosino, Teresa; Rosaria Rubulotta, Maria; Setola, Sergio Venanzio; Mattace Raso, Mauro; Maio, Francesca; Raiano, Concetta; Siani, Claudio; et al.
Abstract: To compare diagnostic performance of contrast‐enhanced dual‐energy digital mammography (CEDM) and digital breast tomosynthesis (DBT) alone and in combination compared to 2D digital mammography (MX) and dynamic contrast‐enhanced MRI (DCE‐MRI) in women with breast lesions. We enrolled 100 consecutive patients with breast lesions (BIRADS 3‐5 at imaging or clinically suspicious). CEDM, DBT, and DCE‐MRI 2D were acquired. Synthetized MX was obtained by DBT. A total of 134 lesions were investigated on 111 breasts of 100 enrolled patients: 53 were histopathologically proven as benign and 81 as malignant. Nonparametric statistics and receiver operating characteristic (ROC) curve were performed. Two‐dimensional synthetized MX showed an area under ROC curve (AUC) of 0.764 (sensitivity 65%, specificity 80%), while AUC was of 0.845 (sensitivity 80%, specificity 82%) for DBT, of 0.879 (sensitivity 82%, specificity 80%) for CEDM, and of 0.892 (sensitivity 91%, specificity 84%) for CE‐MRI. DCE‐MRI determined an AUC of 0.934 (sensitivity 96%, specificity 88%). Combined CEDM with DBT findings, we obtained an AUC of 0.890 (sensitivity 89%, specificity 74%). A difference statistically significant was observed only between DCE‐MRI and CEDM ( P  = .03). DBT, CEDM, CEDM combined to tomosynthesis, and DCE‐MRI had a high ability to identify multifocal and bilateral lesions with a detection rate of 77%, 85%, 91%, and 95% respectively, while 2D synthetized MX had a detection rate for multifocal lesions of 56%. DBT and CEDM have superior diagnostic accuracy of 2D synthetized MX to identify and classify breast lesions, and CEDM combined with DBT has better diagnostic performance compared with DBT alone. The best results in terms of diagnostic performance were obtained by DCE‐MRI. Dynamic information obtained by time‐intensity curve including entire phase of contrast agent uptake allows a better detection and classification of breast lesions.